Whole-exome sequencing of 14 389 individuals from the ESP and CHARGE consortia identifies novel rare variation associated with hemostatic factors. Issue 18 (12th May 2022) - Pankratz, Nathan; Wei, Peng; Brody, Jennifer A; Chen, Ming-Huei; de Vries, Paul S; Huffman, Jennifer E; Stimson, Mary Rachel; Auer, Paul L; Boerwinkle, Eric; Cushman, Mary; de Maat, Moniek P M; Folsom, Aaron R; et al.
Abstract: Plasma levels of fibrinogen, coagulation factors VII and VIII and von Willebrand factor (vWF) are four intermediate phenotypes that are heritable and have been associated with the risk of clinical thrombotic events. To identify rare and low-frequency variants associated with these hemostatic factors, we conducted whole-exome sequencing in 10 860 individuals of European ancestry (EA) and 3529 African Americans (AAs) from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and the National Heart, Lung and Blood Institute's Exome Sequencing Project. Gene-based tests demonstrated significant associations with rare variation (minor allele frequency < 5%) in fibrinogen gamma chain ( FGG ) (with fibrinogen, P  = 9.1 × 10 −13 ), coagulation factor VII ( F7 ) (with factor VII, P  = 1.3 × 10 −72 ; seven novel variants) and VWF (with factor VIII and vWF; P  = 3.2 × 10 −14 ; one novel variant). These eight novel rare variant associations were independent of the known common variants at these loci and tended to have much larger effect sizes. In addition, one of the rare novel variants in F7 was significantly associated with an increased risk of venous thromboembolism in AAs (Ile200Ser; rs141219108; P  = 4.2 × 10 −5 ). After restricting gene-based analyses to only loss-of-function variants, a novel significant association was detected and replicated between factor VIII levels and a stop-gain mutation exclusive to AAs (rs3211938) in CD36 molecule ( CD36 ). This variant has previously been linked to dyslipidemia but not with the levels of a hemostatic factor. These efforts represent the largest integration of whole-exome sequence data from two national projects to identify genetic variation associated with plasma hemostatic factors.